A guide to indoor spiders - Gray, Alex, author; Hufbauer, Ruth, advisor; Camper, Matt, committee member; Stachniak, Matthew, committee member (Colorado State University. Libraries, 2026)
Common house spiders have been studied and researched extensively since roughly the 1900s. While most academic studies focus on scientific research, case studies, and experiments, on these common spiders, there are written comprehensive guides for the public that feature an abundance of spider species. These guides mainly focus on identification and global distribution of common house spiders. The primary goal of the thesis is to help alleviate the fear surrounding spiders by providing positive exposure to them for households in northern Colorado. The thesis serves as a guide for identification, behavior, bite risk and effects, and describes the most common medically significant spiders in Northern Colorado. It compiles this information in a format designed to be accessible to the public, especially for those with arachnophobia, to help ease fears and clear misconceptions about spiders. For this thesis, I primarily focused on Weld and Larimer counties for the most common types of house spiders. The spider species in Northern Colorado were identified through online observations on iNaturalist in Larimer and Weld counties of Colorado. Field data were also factored into the thesis, with the data consisting of spiders that were hand-collected in homes in Larimer County, in the city of Fort Collins. This thesis aims to provide the public with more knowledge about the true effects of common spider bites, accurate spider behavior, and to clarify misconceptions about commonly feared spiders such as the "hobo spider," yellow sac spider, wolf spider, brown recluse, and black widow.
Keywords: spiders; house spiders; Arachnophobia; spider behavior; spider bites; northern Colorado; Larimer County; Weld County; entomology; arachnology